Response to intradermal autologous platelet rich plasma injection in refractory dermal melasma: Report of two cases - Yew, C.H.; Ramasamy, T.S.; Amini, F. (Faculty of Medicine, University of Malaya, 2015)
Refractory dermal melasma is resistant to conventional treatment. Platelet rich plasma (PRP) may help to reduce the pigmentation of melasma. We present a case report on the clinical outcome of 2 patients with melasma, given PRP, as an adjunct therapy. PRP was administered at a monthly interval for 2 sessions in combination with a monthly Q-switched Nd Yag laser treatment and topical alpha arbutin application. A modified melasma area and severity index (MASI) was evaluated by two dermatologists who were blinded. At the follow up on the 3rd months, the MASI score was reduced by mean 33.5% for case 1 and 20% for case 2. There were no clinical complications for case 1. However recurrence of melasma was noted in case 2 by a worsening of the MASI score mean to 53% at the sixth months follow up. In conclusion, intradermal PRP injection as an adjunct to the conventional treatment of melasma presented with differing results in two cases.